COVID‐19 mRNA vaccine‐related interstitial lung disease: Two case reports and literature review. Issue 4 (23rd March 2022) - So, Clara; Izumi, Shinyu; Ishida, Akane; Hirakawa, Ryo; Kusaba, Yusaku; Hashimoto, Masao; Ishii, Satoru; Miyazaki, Hideki; Iikura, Motoyasu; Hojo, Masayuki
Abstract: The Pfizer‐BioNTech mRNA vaccine (BNT162b2) is an effective and well‐tolerated coronavirus disease 2019 (COVID‐19) vaccine. However, rare adverse events have been reported. We report two cases of COVID‐19 mRNA vaccine‐related interstitial lung disease (ILD). A 67‐year‐old man and a 70‐year‐old man with underlying ILD presented to our hospital with a few days of fever and respiratory symptoms after receiving the BNT162b2 vaccine. Drug‐related pneumonitis due to the COVID‐19 mRNA vaccine was diagnosed. One case was diagnosed with lymphocytic alveolitis by bronchoalveolar lavage fluid and transbronchial lung cryobiopsy. Both patients were successfully treated with corticosteroids, and they attended outpatient clinics thereafter. Although the safety and efficacy of COVID‐19 vaccines have been established, further studies are needed to estimate long‐term data and reports of rare adverse reactions. We present the clinical course of two cases, review previously published case reports on COVID‐19 mRNA vaccine‐related ILD and discuss the relevant findings. Abstract : The Pfizer‐BioNTech mRNA vaccine (BNT162b2) is an effective and well‐tolerated coronavirus disease 2019 (COVID‐19) vaccine. However, rare adverse events have been reported. We report two cases of COVID‐19 mRNA vaccine‐related interstitial lung disease.